The Use of Intellectual Measures in the Analysis of Metacognitive Monitoring of Children - Zampieri, Marília (2013)
Metacognitive monitoring is one component of metacognition. It is assessed either through self-report instruments or judgments. The aim of the present study was to investigate metacognitive monitoring of children during the execution of three subtests of an intelligence battery, based on the Cattell-Horn-Carroll intelligence model. Participants answered the subtests and were asked to estimate their performance. Results indicate that participants already had metacognitive abilities in their repertoire, and some monitoring measures were significantly better for the subtest Performance on Mathematics. The data of this study are relevant in confirming information from the international literature using a Brazilian sample, and in discussing the importance of incentives for metacognitive training.